2010
DOI: 10.1061/(asce)su.1943-5428.0000020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Strain and Rotation Tensors in Geodetic Network

Abstract: This article deals with the characteristics of deformation of a body or a figure represented by discrete points of geodetic network. In each point of geodetic network kinematic quantities are considered: normal strain, shear strain and rotation. They are computed from strain and rotation tensors represented by displacement gradient matrix on the basis of known point displacement vector. Deformation analysis requires the appropriate treatment of kinematic quantities. Thus statistical properties of each quantity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
3
Order By: Relevance
“…Caso desejado, pode-se adotar uma estratégia de ponderação para os elementos do vetor de deslocamentos (u), introduzindo uma matriz peso na Equação (5) em função das distâncias entre os diferentes pontos considerados (ver, por exemplo, VANÍČEK et al, 1996;MARJETIČ et al, 2010).…”
Section: Extensão Do Método De Análise De Robustez Para Múltiplos Out...unclassified
See 1 more Smart Citation
“…Caso desejado, pode-se adotar uma estratégia de ponderação para os elementos do vetor de deslocamentos (u), introduzindo uma matriz peso na Equação (5) em função das distâncias entre os diferentes pontos considerados (ver, por exemplo, VANÍČEK et al, 1996;MARJETIČ et al, 2010).…”
Section: Extensão Do Método De Análise De Robustez Para Múltiplos Out...unclassified
“…A análise de robustez vem sendo largamente investigada desde o trabalho pioneiro de Vaníček et al (1991), podendo-se citar os estudos de Vaníček et al (1996) em redes geodésicas de grande extensão, Seemkooei (2001aSeemkooei ( , 2001b na etapa de planejamento, Vaníček et al (2001) e Hsu e Li (2004) em redes geodésicas horizontais, Berber (2006) no campo de deslocamentos dos vértices, Hsu et al (2008) e Vaníček et al (2008) em redes tridimensionais, Marjetič et al (2010) sobre as propriedades estatísticas dos tensores, no caso de observações correlacionadas, e no âmbito nacional, Klein et al (2013) sobre a acurácia de redes horizontais e Cavalheri e Chaves (2014) sobre a robustez das estações da rede GNSS-SP.…”
Section: Introductionunclassified
“…Ugotavljamo statistično značilnost deformacij in rotacij. Osnovni pogoj za to je seveda poznavanje porazdelitev posameznih parametrov (Marjetič et al, 2010).…”
Section: Uvodunclassified
“…Uncertainties for strains and rotations shown in Appendix 12 were empirically derived by Monte Carlo simulation [Cox and Siebert, 2006;Papadopoulis and Yeung, 2001]. Marjetič et al [2010] have shown that this is an appropriate method for determining the statistical properties of strain and rotation tensors in a geodetic network, but it should be noted that this method only applies to the specific combination of sites used in each region, and, as observed above, changes in the selection of sites can have much greater effects on the results than these uncertainty values imply.…”
Section: Secular Velocitiesmentioning
confidence: 99%
“…For small regional areas, over which it appears that displacement fields are relatively uniform, we might consider the average displacement field D to comprise a tensor of small strains and small rotations. This tensor can then be decomposed into the symmetric (strain) and the asymmetric (rotation) components [Marjetič et al, 2010]: Also shown in Appendix 12 is an analysis for the combination of the northeast coast and Mahia-Gisborne regions. This illustrates that the strain rate magnitudes and rotation rates are very sensitive to the number of sites selected.…”
Section: Secular Velocitiesmentioning
confidence: 99%